Analysis Quality of Equation Items in Learning Evaluation for Physics Subject in High Schools of Mentawai Island Regency - Fredy Pratama; Yenni Darvina (PILLAR OF PHYSICS EDUCATION, 2023)
The process of evaluating learning outcomes is one thing that cannot be separated by a teacher to reveal the extent to which students receive and learning understanding given in class. To be able to produce good measurable values, the instrument used must also be good. A good instrument must have standards that have been tested as a whole, in this case the question sheets used as instruments in the evaluation process must be measurable and tested in consist of validity, reliability, level of difficulty, and diffrentitation. This research is a descriptive research with a qualitative approach by taking several samples of schools in the Mentawai Islands District. The analysis was conducted on the evaluation instrument or sheet used by teachers in schools in the form of 4 aspects analysis, namely validity, reliability, level of difficulty, and diffrentitation. The research purpose was to be able to find out to what extent the quality level of the instrument or evaluation sheet used by teachers in the sampled schools. The research results obtained showed that of the 4 samples of schools that were taken and examined, it shows that in terms of validity for the whole school it can be declared valid with a range of high to low categories. Meanwhile, for the reliability aspect, it was noted that 3 out of 4 schools had reliable instruments, while 1 school was classified as unreliable. For aspects by level of difficulty and item differentitation, it is still classified as very low because there are still less than 50% of the questions that are of good quality and have sufficient differentitation.